BEYOND COMPLIANCE: DISCIPLINE, FACILITIES, CREATIVITY, AND TEAMWORK AS JOINT DRIVERS OF EMPLOYEE PERFORMANCE - Yandra Rivaldo (LPPM Universitas Ibnu Sina, 2025)
This study examines the joint and partial effects of work discipline, work facilities, creativity, and teamwork on employee performance at PT. Bakri Karya Sarana, a logistics and construction-equipment trading firm in Batam, Indonesia. Small and medium-sized trading enterprises in Indonesia's outer-island industrial zones face persistent human-resource constraints, yet the combined behavioral and structural drivers of employee performance in such firms remain under-researched relative to large corporates. A quantitative associative design was used, with a census of all 75 permanent employees as respondents. Data were collected through a structured Likert-scale questionnaire and analyzed using multiple linear regression in SPSS 23, following classical assumption testing. The results show that work discipline (t = 8.230; p = .000), work facilities (t = 3.020; p = .003), creativity (t = 2.865; p = .002), and teamwork (t = 3.246; p = .001) each have a positive and significant partial effect on employee performance, and the four variables jointly explain 85.0 percent of the variance in employee performance (R² = .850; F = 95.130; p = .000). Work discipline is the most dominant predictor (β = .512), followed by creativity (β = .210), work facilities (β = .221), and teamwork (β = .184). The findings indicate that performance in this firm rests primarily on behavioral compliance, reinforced by adequate physical infrastructure and a working culture that supports both individual initiative and collaboration, with implications for human-resource practice in comparable trading and logistics SMEs.